50 likes | 118 Views
Solve using substitution . 8x – 2y = 10 2x + y = 13 -4x + y = 9 x + 6y = 34. Solve using substitution . x – 2y = 10 2x + y = 16 -14x + 2y = 64 4x + 6y = 54. Solve using elimination. x – 2y = 10 2x + y = 16 -14x + 2y = 64 4x + 6y = 54.
E N D
Solve using substitution • 8x – 2y = 10 2x + y = 13 • -4x + y = 9 x + 6y = 34
Solve using substitution • x – 2y = 10 2x + y = 16 • -14x + 2y = 64 4x + 6y = 54
Solve using elimination • x – 2y = 10 2x + y = 16 • -14x + 2y = 64 4x + 6y = 54
Solve by graphing, substitution, and elimination x – 2y = -12 2x + y = 26
Solve by graphing, substitution, and elimination -14x + 2y = 64 4x + 6y = 54